Aspek Maqāṣid al-Kulliyyah dan al-Juziyyah dalam Penetapan Awal Waktu Shalat Shubuh dan Isya’ - Qulub, Siti Tatmainul; Sanuri, Sanuri (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
Determining the beginning of prayer times, especially Fajr and Isha', has become a debate among astronomers and religious institutions related to the technical aspects of astronomy and Islamic law, especially in relation to maqāṣid al-sharī‘ah. This article examines the differences between the results of Tono Saksono's research and the provisions of the Indonesian Ministry of Religious Affairs regarding the height of the sun, which show a time difference of around 26 minutes. Using the maqāṣid al-sharī‘ah approach, this article evaluates the implications of maslahat and mafsadah from these differences and assesses the aspects of maqāṣid al-kulliyyah and maqāṣid al-juziyyah in determining the beginning of prayer times. This study uses a qualitative method, which collects data through literature studies and analyzes them in depth using a descriptive-analytical approach. The results of the study indicate that in determining the beginning of Fajr and Isha's prayers, the approach of the majority of astronomers prioritizes maqāṣid al-kulliyyah (universal benefits) for Muslims. Tono Saksono's opinion, although scientifically based, tends to lead to maqāṣid al-juziyyah, which has the potential to cause confusion and disrupt the unity of the community. Therefore, the integration of science and sharia that pays attention to collective interests is key in determining the right prayer times and is accepted by the community.